Islamic Religious Education Teacher's Efforts to Prevent Radicalism in Indonesia: A Genealogical Analysis - Rijal, Akh Syaiful; Muhammad Thohir; Aliwafa; Mohammad Davoudi; Imam Syafi’i (State Islamic Institute of Madura, 2024)
Radicalism is very contradictory to the values ​​of Islamic teachings. Islam upholds the principles of tolerance, peace, and the principle of respecting one's beliefs. This study aims to analyze and find ideal conceptual ideas for preventing student radicalism through the role of teachers in schools from a genealogical perspective. This study uses a qualitative approach with a type of descriptive-analytic. In order to track historical traces and provide answers to the radicalism issue, the genealogical data analysis technique is utilized to examine the content of pertinent sources. The results of this study indicate that, genealogically, Islamic Religious Education teachers in schools have an important role in preventing radicalism because the main mission of Islamic Religious Education teachers is to teach Islam contextually, Islamic tolerance, and peace-loving Islam through efforts to internalize Islamic teachings that are in line with a sense of nationalism so that a generation with noble character is formed. In addition, Islamic Religious Education teachers also carry out the learning process by adhering to 5 main principles, namely respect for others, moderation, respect for creators, tolerance, and fairness.